Kingdom of Saudi Arabia - Ismail, Russayani; Yew, Meng Lai; Ayub, Zainal Amin; Ahmad, Abdul Razak; Chang, Da Wan (Springer, 2016)
Since the discovery of oil in 1936, the Kingdom of Saudi Arabia is currently the leader in the international oil industry.The revenue generated from oil has enabled the country to intensify its development initiatives through economic diversification.In a knowledge-based economy , the country realised that the sustainability of future growth mainly depends on the ability of its citizen to fully equip themselves with the appropriate skills, knowledge and competencies, and this can only be achieved through an investment in human capital, in particular higher education.For the last two decades, the intensification of higher education in the Kingdom has indeed taken place in line with the growth of information technology and globalisation. Attention towards quality and standard become a key concern of the government as this will ensure the sustainability of the higher education sector in the Kingdom.Notwithstanding the vast potential opportunities to be explored in higher education sector in the country, the socio-political climate may hinder the development and progress of this sector.